Metagenomic Analyses of Gut Bacteria of Two Sandfly Species from Western Ghats, India, Differing in Their Vector Competence for Leishmaniasis - Anns Tom; Nanda Kumar Yellapu; Manju Rahi; Prasanta Saini (Microorganisms)
Phlebotomine sandflies are the primary vectors of Leishmania parasites, the causative agents of leishmaniasis. In India, Phlebotomus argentipes is the confirmed vector of Leishmania donovani. The sandfly gut microbiota plays a crucial role in Leishmania development and transmission, yet it remains largely understudied. This study used a metagenomic approach targeting the V3–V4 region of the 16S rRNA gene to compare the gut bacterial communities of P. argentipes and Sergentomyia babu prevalent in Kerala. A total of 18 distinct bacterial phyla were identified in P. argentipes, and 14 in S. babu, both dominated by Proteobacteria, Actinobacteria, and Firmicutes. A total of 315 genera were identified in P. argentipes, with a high relative abundance of Pseudomonas (6.3%), whereas S. babu harbored 327 genera, with Pseudomonas showing a higher relative abundance of 11%. Unique to P. argentipes, bacterial phyla such as Fusobacteria, Armatimonadetes, Elusimicrobia, Chlamydiae, and Crenarchaeota were identified, whereas Chlorobi was specific to S. babu. Additionally, 145 species were identified in P. argentipes, compared to 164 species in S. babu. These findings provide a comparative baseline of gut microbial diversity between vector and non-vector sandfly species, offering a foundation for future functional investigations into vector competence.